2012
DOI: 10.1016/j.yexcr.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Desmoglein 3 acting as an upstream regulator of Rho GTPases, Rac-1/Cdc42 in the regulation of actin organisation and dynamics

Abstract: Desmoglein 3 (Dsg3), a member of the desmoglein sub-family, serves as an adhesion molecule in desmosomes. Our previous study showed that overexpression of human Dsg3 in several epithelial lines induces formation of membrane protrusions, a phenotype suggestive of Rho GTPase activation. Here we examined the interaction between Dsg3 and actin in detail and showed that endogenous Dsg3 colocalises and interacts with actin, particularly the junctional actin in a Rac1-dependent manner. Ablation of Rac1 activity by do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 41 publications
9
60
0
Order By: Relevance
“…These data suggest that adducin controls keratinocyte cohesion specifically by regulating desmosomal Dsg3 levels. Previously, a direct interaction of Dsg3 and actin was demonstrated, however, in the non-cytoskeletal pool only and not in Dsg3 connected to the cytoskeleton (24). Nevertheless, a direct regulation of Dsg3 by adducin, i.e.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These data suggest that adducin controls keratinocyte cohesion specifically by regulating desmosomal Dsg3 levels. Previously, a direct interaction of Dsg3 and actin was demonstrated, however, in the non-cytoskeletal pool only and not in Dsg3 connected to the cytoskeleton (24). Nevertheless, a direct regulation of Dsg3 by adducin, i.e.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, for RhoA-mediated protection against autoantibody-induced loss of cell cohesion a requirement of cortical actin polymeri-zation has been demonstrated (23). Concomitantly, a recent study reported a direct association of Dsg3 with actin and its involvement in actin dynamics (24).…”
mentioning
confidence: 96%
“…In some cases, a specifi c signaling molecule associates with the Dsg3 complex. This has been shown for Rho GTPases and Src (Tsang et al, 2012a(Tsang et al, , 2012b. PKC has been located at the desmosomal plaque via electron microscopy (Garrod et al, 2005), and may directly bind to desmosomal proteins.…”
Section: Signaling Function Of Desmosomal Cadherinsmentioning
confidence: 81%
“…RhoA is inhibited in response to pemphigus autoantibodies in p38MAPK-dependent manner and activation of this GTPase blocked blister formation and enhanced insertion of keratin 14 at cell junctions (Waschke, 2008). Recently, RhoA, Rac1, and Cdc42 were shown to directly bind to Dsg3, at least in the non-desmosomal fraction, further indicating that the desmosomal cadherins regulate Rho GTPases (Tsang et al, 2012a). Keratin retraction downstream of p38MAPK is dependent on EGF-R activation, (Figure 1) (Bektas et al, 2013).…”
Section: Mechanisms Regulating the Cytoskeletal Anchorage Of Desmosomesmentioning
confidence: 98%
See 1 more Smart Citation